Integrating alternative and complementary medicine in the management of epilepsy and its comorbidities in low- and middle-income settings - Kariuki, SM; Newton, CRJC (Elsevier, 2024)
Traditional/alternative and complementary medicine (TCM) encompasses products, practices and practitioners that do not form part of conventional treatment and are not an integral part of the main health care systems. They are very common in the management of epilepsy and mental health conditions, particularly in low- and middle-income countries (LMIC). For instance, in a population-based survey in Africa, over 70% of people with epilepsy had visited a traditional health practitioner before the survey, with similarly high estimates reported in Asia and South America. Accessibility, cultural appropriateness/alignment, non-response to conventional (biomedical) medicine, and exercise of control over one's treatment were some of the reasons TCM was preferred over conventional medicine. There is also emerging evidence that TCM products administered alone or together with anti-seizure medications result in improvement in seizure control, psychiatric comorbidities, and quality of life. Most of the convincing evidence is from biological-based therapies for example, multivitamin supplementation, ketogenic diet and cannabidiol extracts. Mind-based therapies e.g. Yoga and whole-body systems therapies e.g. Ayurdelic and Traditional Chinese Medicine have also generated interest in epilepsy care. There is a paucity of effectiveness studies of these therapies in LMIC such as Africa, where capacity to take these products through clinical trials is limited. There are however serious concerns on reliability of reported findings because of inadequate randomization, and small sample sizes, and concerns on quality and safety owing to lack of standardization of bioactive compounds, accidental or intention botanical substitution of products and unhygienic handling. There is growing interest in TCM worldwide because of its economic potential, concerns on safety and quality and potential for integration into the health care systems. There is urgent need to develop and implement national TCM regulatory policies and programmes aimed at expanding the knowledge base and providing guidance on quality assurance standards. However, LMIC continue to lag in implementation of these policies and guidelines, especially in the areas of research and development and regulation of TCM practice. Working with stakeholders, countries are advised to assess their own national situations in relation to TCM, and then develop practical solutions to accommodate these approaches. For instance, conduct surveys on benefits and risks of TCM in the management of epilepsy in the local context and use this information to promote appreciation of a role for TCM, which will ease integration into the main health systems.